경남 함안의 서원판본에 대한 연구 - 윤상기 (서지학연구, 0(44), 2009)
이 글은 1910년 당시의 경남 咸安郡에 所在했거나 소재한 적이 있었던 서원들에서 그때까지 발행했거나 발행했을 가능성이 있는 판본들에 대하여 살펴보고자 한 것이다. 해당되는 서원은 모두 19개이다. 이들 중 5개 서원에서 6종의 판본을 발행했고, 3종의 판본을 발행했을 가능성이 있다. 발행사실이 확실한 것은 德淵書院에서 발행한 「武陵雜稿」, 西山書院에서 발행한 「漁溪先生集」, 「咸安趙氏十忠實錄」(1784序) 및 「咸安趙氏十忠實錄」(1794序), 松汀書院에서 발행한 「金羅傳信錄」 및 廬陽書院에서 발행한 「晩黙堂先生文集」이고, 발행했을 가능성이 있는 것은 德巖書院의 「大笑軒先生逸稿」, 西山書院의 「損庵集」 및 松汀書院의 「澗松先生文集」이다. 이들 판본들에 대해서는 서지사항을 정밀기술하고 서원판본임을 밝히거나 발행 가능성을 제시했다. 발행했을 가능성이 있는 판본들까지 포함한 전체 9종의 판본들을 분석하여 다음과 같은 몇 가지 점들을 밝혀냈다. 첫째, 集部의 別集類가 6종이고 史部의 傳記類가 3종으로 集部의 別集類가 다수이다. 둘째, 모두 목판본이다. 셋째, 18C에 발행된 것이 6종이고 19C에 발행된 것이 3종으로 주로 18C에 발행되었다. 넷째, 6종의 저자가 관련 서원의 배향자 본인들이고 3종의 편․저자는 배향자의 후손들로서 모두 관련 서원의 배향자들과 직․간접으로 관련이 있다. The purpose of this study is to investigate the publications, either published or assumed to be published by seowons(서원) located in Haman(함안), Gyeongsangnam-do(경상남도) by the year 1910. Out of the nineteen seowons, five published six books and might have published three more books. The books confirmed to be published by seowons are as follows: Mureung japgo(「武陵雜稿」) by Deogyeon Seowon(德淵書院), Eogye-seonsaeng jib(「漁溪先生集」), Haman Jo-ssi sipchung sillok(foreword in 1784)(「咸安趙氏十忠實錄」(1784序)), and Haman Jo-ssi sipchung sillok(foreword in 1794)(「咸安趙氏十忠實錄」(1794序)) by Seosan Seowon(西山書院), Geumna jeonsinrok(「金羅傳信錄」) by Songjeong Seowon(松汀書院) and Manmukdang-seonsaeng munjib(「晩黙堂先生文集」) by Yeoyang Seowon(廬陽書院). And Daesoheon-seonsaeng ilgo(「大笑軒先生逸稿」), Sonam jib(「損庵集」) and Gansong-seonsaeng munjib(「澗松先生文集」) are assumed to have been published by Deogam Seowon(德巖書院), Seosan Seowon(西山書院), and Songjeong Seowon(松汀書院), respectively. In this research, bibliographical information of these books have been described in detail and it is also confirmed that they were published either certainly or possibly by seowons. An analysis of these nine books shows the following characteristics: First, six books are categorized into individual works(別集) of the class of Collection of Works(集部), and three were categorized into biography(傳記) of the class of History(史部). Second, they were all printed with wooden movable types(목판본). Third, six books were published in the 18the century and three in the 19the century. Forth, they are all directly or indirectly related to the worshipers of related seowon. Six of them were works of the scholars enshrined at those seowons and three were written or edited by their descendants. KCI Citation Count: 8